The Impact of Motivation on the Academic Performance of University Students - Dokhykh, Raihanah Ali (Journal of Humanities & Social Sciences, 2021)
This study evaluates how motivation influences the academic performances of university students. The sample includes 400 higher education students attending different universities in Saudi Arabia. The questionnaire was the data gathering method that was chosen by the researcher to complete this study. The study reveals that both intrinsic and extrinsic motivations positively impact the academic performance of students. Academic performance increased by a percentage increase of between 23% and 34 %. Overall, the model showed a significant jump (p
Keywords: university students; Saudi Arabia; Higher Education